(untitled) - Strunk, William (New York, 1959)
The book consists of a short introduction, eight rules of usage, ten principles of composition, a few matters of form, a list of words and expressions commonly misused, a list of words commonly misspelled.
Keywords: English language,Tiếng Anh; Rhetoric,Tu từ học